A Study on Microwave Absorption Properties of Carbon Black and Ni0.6Zn0.4Fe2O4 Nanocomposites by Tuning the Matching-Absorbing Layer Structures - Idza Riati, Ibrahim; Khamirul Amin, Matori; Ismayadi, Ismail; Zaiki, Awang; Siti Nor Ain, Rusly; Rodziah, Nazlan; Fadzidah, Mohd Idris; Muhammad Misbah, Muhammad Zulkimi; Nor Hapishah, Abdullah; Muhammad Syazwan, Mustaffa; Farah Nabilah, Shafiee; Mehmet, Ertugrul (2020)
Microwave absorption properties were systematically studied for double-layer carbon black/epoxy resin (CB) and Ni0.6Zn0.4Fe2O4/epoxy resin (F) nanocomposites in the frequency range of 8 to 18 GHz. The Ni0.6Zn0.4Fe2O4 nanoparticles were synthesized via high energy ball milling with subsequent sintering while carbon black was commercially purchased. The materials were later incorporated into epoxy resin to fabricate double-layer composite structures with total thicknesses of 2 and 3 mm. The CB1/F1, in which carbon black as matching and ferrite as absorbing layer with each thickness of 1 mm, showed the highest microwave absorption of more than 99.9%, with minimum reflection loss of −33.8 dB but with an absorption bandwidth of only 2.7 GHz. Double layer absorbers with F1/CB1(ferrite as matching and carbon black as absorbing layer with each thickness of 1 mm) structure showed the best microwave absorption performance in which more than 99% microwave energy were absorbed, with promising minimum reflection loss of −24.0 dB, along with a wider bandwidth of 4.8 GHz and yet with a reduced thickness of only 2 mm.